2021
DOI: 10.1111/and.14034
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus infection and sperm quality: A systematic review and a meta‐analysis

Abstract: Human papillomavirus (HPV) has a high incidence rate in both males and females. HPV infection in women has been shown to affect fertility and lead to foetal death and pregnancy loss. However, research on HPV infection in men is limited. The aim of this study was to study the effect of HPV infection in semen on sperm quality and present the findings of previous studies through a meta‐analysis. Databases including PubMed, MEDLINE, EMBASE, Web of Science, Cochrane Library, WanFang data and China National Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…In conclusion, while numerous reviews analyzing the correlation between HPV and male infertility seem to find agreement (84)(85)(86)(87), there are few analyses that speculate about the correlation between HPV and female or couple infertility (64,88). The few reviews available do not seem to find agreement with each other and with many other published studies.…”
Section: Discussionmentioning
confidence: 79%
“…In conclusion, while numerous reviews analyzing the correlation between HPV and male infertility seem to find agreement (84)(85)(86)(87), there are few analyses that speculate about the correlation between HPV and female or couple infertility (64,88). The few reviews available do not seem to find agreement with each other and with many other published studies.…”
Section: Discussionmentioning
confidence: 79%
“…One possible explanation for the mechanisms involved could be that HPV-DNA exposure causes SDF and that HPV could be located at the equatorial region of the sperm head and lead to reduced sperm parameters. 83 Most published studies showed a deleterious impact of HPV on sperm progressive motility but did not investigate the impact of HPV infection on sperm vitality. [84][85][86] Interestingly, Boeri et al 84 found that HPV positive men presented with higher SDF rates than those with a negative HPV test, suggesting an increased ROS production and a potential alteration of sperm vitality.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Testicular Viral infection X X Lorusso et al 71 , Wang et al, 79 Wang et al, 83 Erbay et al 94 Varicocele X X Vivas-Acedo et al, 64 Cho et al 68 Dysthyroidism X X Abalovich et al, 58 La Vignera et al, 60 Krassas et al 61 Environmental exposure X X Hardneck et al, 138 Pizzol et al, 144 Martini et al, 129 du Plessis et al 134 Post-testicular ADPKD X X Vora et al, 156 Mieusset et al 157 ASA X Kay et al, 105 Matson et al 106 Idiopathic X X Nduwayo et al, 38 Correa-Pérez et al 128 Mixed Smoking X X Mostafa et al, 121 Hamad et al 120 SCI X X X X Mallidis et al, 39 Brackett et al 154 Age X X Condorelli et al, 63 Brahem et al 117 Genital infection X X X Sanocka-Maciejewska et al, 46 Liu et al 49 Obesity X X X X Salas-Huetos et al, 108 Andersen et al 109 Abbreviations: ADPKD, autosomal dominant polycystic kidney disease; ASA, antisperm antibodies; SCI,spinal cord injury.…”
Section: Blood-testis Barrier Disruption Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION: Most men of reproductive age in high or midst-earning nations own cell phones, and with this increase in cellular phone management, there is egoism over the crucial adverse effects of cell phone visibility on a man's being 31 . Cellular telephones produce electromagnetic radiation (EMR), the lowest-stage radiofrequency (RF), at a volume between 800 and 2200 MHz, which the human body can absorb 32 . Cell phones are legally limited to a particular absorption amount (SAR) of 2.…”
mentioning
confidence: 99%